(untitled) (Research, Society and Development, 2021)
Objective: Describe how students and teachers experience remote work during a pandemic. Methods: This is an experience report, with a critical-reflective approach, carried out in a virtual environment through digital platforms, available on the web for free. Results: The results were compiled into two themes: 1. Make time more flexible to balance work and family life; 2. Exercising autonomy and integration between technology and education. Final considerations: The development of writing during social isolation provided enriching experiences for the entire team. The path followed to carry out all activities remotely, in a context never experienced by the majority of the executing team, presents difficulties and obstacles, but the positive points strengthen the work team, whether through the discovery of new educational elements, autonomy and cooperation or through interactivity and exchange of knowledge. Thus, the context demanded adaptation to new teaching-learning strategies with a view to producing scientific knowledge through the use of technological tools and social networks, in order to promote communication and the development of this experience report.